Impaired natural killer cell‐induced antibody‐dependent cell‐mediated cytotoxicity is associated with human immunodeficiency virus‐1 disease progression - Jia, M.; Li, D.; He, X.; Zhao, Y.; Peng, H.; Ma, P.; Hong, K.; Liang, H.; Shao, Y. (Clinical and experimental immunology, 2013)
Summary This study evaluates the correlation between natural killer (NK) cell function and human immunodeficiency virus (HIV)‐1 disease progression in 133 untreated HIV‐1 positive Chinese subjects, including 41 former plasma donors (FPDs) and 92 men who have sex with men, and 35 HIV‐negative controls. Flow cytometry was used to determine the abundance of NK cell subsets, the expression levels of receptor species, human leucocyte antigen (HLA) genotyping and the antibody‐dependent cell‐mediated cytotoxicity (ADCC) responses of NK cells. We observed a decreased expression of CD56dimCD16+ NK cell subsets and an increased expression of CD56−CD16+ with HIV‐1 infection. As well, the expression of activating and inhibitory receptors increased significantly in NK cells, but CD16 receptor levels and the NKG2A/NKG2C ratio were down‐regulated with HIV‐1 infection. ADCC responses were higher in elite controllers than in all other groups, and were correlated inversely with HIV‐1 viral load but correlated positively with CD4 count only in FPDs. Furthermore, individuals infected for < 1 year have lower ADCC responses than those infected for > 1 year. We also observed a negative association between ADCC responses and viral load in those who carry the HLA‐A*30/B*13/Cw*06 haplotype. The positive correlation between CD16 expression and ADCC responses and a negative correlation trend between CD158a and ADCC responses were also observed (P = 0·058). Our results showed that the ADCC response is associated with patients' disease status, receptor expression levels, infection time and specific HLA alleles, which indicates that ADCC may offer protective effects against HIV‐1 infection.